Natriorexigenic effect of baclofen is reduced by AT(1) receptor blockade in the lateral parabrachial nucleus - Silva, Camila Zambone Cardoso da [UNESP] (2011)
GABA(A) and GABA(B) receptors activation with agonists muscimol and baclofen, respectively in the lateral parabrachial nucleus (LPBN), induces water and hypertonic NaCl intake in rats. The purpose of this study was to examine the effects of previous injections of losartan (AT(1) angiotensin receptor antagonist) into the LPBN on 0.3 M NaCl and water intake induced by baclofen injected bilaterally in the same area in fluid replete rats and in rats treated with the diuretic furosemide combined with a low dose of the angiotensin-converting enzyme inhibitor captopril injected subcutaneously. Male Wistar rats with stainless steel cannulas implanted bilaterally into the LPBN were used. Bilateral injections of baclofen (0.5 nmol/0.2 mu l, n=6) into the LPBN in fluid replete rats induced 0.3 M NaCl intake (22.4 +/- 6.5 vs. saline: 0.1 +/- 0.1 ml/210 min) and water intake (14.2 +/- 4.0 vs. saline: 0.6 +/- 0.6 ml/210 min) and pre-treatment of the LPBN with losartan (50 mu g/0.2 mu l,l) reduced 0.3 M NaCl intake (7.4 +/- 7.0 ml/210 min) and water intake (2.8 +/- 2.4 ml/210 min) induced by baclofen. In rats treated with furosemide + captopril, pre-treatment with losartan into the LPBN attenuated the increase in 0.3 M NaCl intake (13.3 +/- 3.2 vs. saline + baclofen: 24.3 +/- 3.9 ml/180 min) and water intake (4.8 +/- 2.1 vs. saline + baclofen: 19.5 +/- 6.6 ml/180 min) produced by baclofen. We conclude that baclofen may produce a non-specific blockade of the inhibitory mechanisms of LPBN (deactivation of LPBN inhibitory mechanisms) and this blockade is facilitated by angiotensin II acting on AT(1) receptors in the LPBN, which drives rats to ingest large amounts of water and hypertonic NaCl independent if rats are fluid depleted or normohydrated. (C) 2011 Elsevier B.V. All rights reserved.